Dipolar particles trapped in a cylindrical pore. (15th March 2023) - Mourad, A.; Mohrbach, H.; Messina, R.
Abstract: A salient effect of strong confinement, especially when quasi one-dimensional, is to drastically alter the phase behavior and concomitantly the physico-chemical properties of a substance encountered in the bulk. The ground state phase diagram of dipolar hard spheres of diameter d as a function of the pore opening, with D being the cylinder diameter of the confining pore, is investigated theoretically. Whereas finding the densest configurations with hard spheres would be a purely geometrical problem, the situation becomes much more intricate with long-ranged anisotropic interactions. As a major finding, long pores prohibit chain undulation ( helicity ) and wall-contact–free ( floating ) linear chain bundles emerge. These results shed light on recent experimental observations with magnetic colloids in microtubes. Applications in other fields are discussed as well.